A resident's perspective on why global health work should be incorporated into family medicine residency training. Issue 1 (1st January 2016) - Sweeney, Sarah
Abstract : Family physicians are well prepared to address global health issues. In this perspective a family medicine resident reflects on her experience working on a global health project in Guatemala and why this type of experience should be incorporated into family medicine residency training.